Oxyresveratrol and its synthetic derivatives on the stimulation of glucose uptake in skeletal muscle cells and the activation of AMPK - Tharita Kitisripanya (2022)
Diabetes mellitus (DM) is a hyperglycemic condition occurring due to insulin resistance or impaired insulin secretion. Structural modifications of natural products are a promising way to discover new lead compounds for DM management. Oxyresvertrol, abundantly found in Artocarpus lacucha Buch. - Ham. heartwood and Morus alba L. wood, exhibited biological activities against metabolic syndromes associated with diseases including DM. Hence, in this study, oxyresveratrol was used as the precursor for its synthetic derivatives. Then, the compound and its nineteen derivatives were investigated for their glucose uptake activities in L6 rat skeletal muscle cells. The results showed that oxyresveratrol and its derivative, 5-carboxy-2,30,4,50-tetrahydroxystilbene, possess a higher glucose uptake activity than metformin. They also elevated AMPK alpha-1 mRNA expression in a dose-dependent manner. Moreover, their binding energy against AMPK active sites was reported, and the finding would be applicable to further investigations of oxyresveratrol, including structure-activity relationship and structural modification.